1995
DOI: 10.1007/bf00187179
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological and ultrastructural study of the developing tendons of the avian foot

Abstract: The aim of the present report is to provide a detailed description of the morphogenesis and initial differentiation of the long tendons of the chick foot, the long autopodial tendons (LAT), from day 6 to day 11 of development. The fine structure of the developing LAT was studied by light and transmission electron microscopy. The characterization by immunofluorescent techniques of the extracellular matrix was performed using laser scanning confocal (tenascin, elastin, fibrillin, emilin, collagen type I, II, III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
52
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 52 publications
7
52
0
Order By: Relevance
“…Nevertheless, we found that the FB1 epitope is localized immunoelectron-microscopically in the bundles of subectodermal microfibrils, and that the electrophoretic mobility and immunohistochemical distribution of the FB1 antigen are indistinguishable from those of JB3 antigen, or chicken fibrillin-2 Rongish et al, 1998). The spatial pattern of the fibers demonstrated in this study also overlaps in part the pattern of elastin immunoreactivity in the limb bud (Hurle et al, 1994;Ros et al, 1995;Hurle and Colombatti, 1996), but appears to be more comparable to the pattern of emilin (Hurle and Colombatti, 1996), which is known to be localized in the elastin-microfibril interface (Bressan et al, 1993). On the basis of these and other findings in this study, we discuss the functional and developmental significance of a parallel spatial array of extracellular subectodermal microfibrils.…”
supporting
confidence: 61%
“…Nevertheless, we found that the FB1 epitope is localized immunoelectron-microscopically in the bundles of subectodermal microfibrils, and that the electrophoretic mobility and immunohistochemical distribution of the FB1 antigen are indistinguishable from those of JB3 antigen, or chicken fibrillin-2 Rongish et al, 1998). The spatial pattern of the fibers demonstrated in this study also overlaps in part the pattern of elastin immunoreactivity in the limb bud (Hurle et al, 1994;Ros et al, 1995;Hurle and Colombatti, 1996), but appears to be more comparable to the pattern of emilin (Hurle and Colombatti, 1996), which is known to be localized in the elastin-microfibril interface (Bressan et al, 1993). On the basis of these and other findings in this study, we discuss the functional and developmental significance of a parallel spatial array of extracellular subectodermal microfibrils.…”
supporting
confidence: 61%
“…Collagen type III is a member of the fibrillar collagen family and the second most abundant collagen molecule in tendon. Studies in skin, tendon, and other tissues indicate a role for collagen type III in regulating fibrillogenesis of collagen type I (Fleischmajer et al, 1988(Fleischmajer et al, , 1990Ros et al, 1995;Liu et al, 1997;Birk and Mayne, 1997). Decorin is a small chondroitin-dermatan sulfate proteoglycan consisting of a core protein and a single glycosaminoglycan chain, and is the most abundant proteoglycan in mature tendon (Goh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Type I collagen is not specific to tendon and is a major component of many other extracellular matrices, because it is also synthesised by skin and cornea fibroblasts, osteoblasts, and odontoblasts. Type I collagen is detected in early chick limb buds and has been described as being associated with the developing limb tendons from E6 (Hurle et al, 1989;Ros et al, 1995). The low abundance fibrillar collagens types III and V are able to form heterotypic fibrils with type I collagen (Canty and Kadler, 2002) and, therefore, are also part of the precise architecture of extracellular matrix of the tendons (Table 1).…”
Section: Molecular Markers Of Tendons During Embryonic Developmentmentioning
confidence: 99%
“…This finding can partly explain the small amount of research on the early steps of tendon development compared with those on muscle and bone development. The glycoprotein tenascin was classically used as a tendon marker during embryonic development (Hurle et al, 1989;Ros et al, 1995;Kardon, 1998); with the limitation that it labels other embryonic structures (such as nerves and perichondrium), making it difficult to follow early steps of tendon development. The discovery that the bHLH transcription factor scleraxis labels tendons, cells of tendon primordia, and probably the tendon progenitor cells (Schweitzer et al, 2001) constituted a breakthrough for research into the embryology of tendons.…”
Section: Molecular Markers Of Tendons During Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation